(untitled) (Itinera, 2012)
This essay aims to the reassessment of Renato Simoni’s work, providing a new reading of his relationship with Giacomo Puccini, further than the undoubtedly very important – as widely studied – composition of Turandot. Although for almost forty years he was, not only the theatre critic for the most important national newspaper (Il corriere della sera), but also one of the greatest representatives of Early Twentieth Century theatre culture and society, few researches are dedicated to Renato Simoni’s activities. Dramatist, critic, librettist and director, Simoni – born in Verona in 1875 and passed away in Milan in 1952, age 67 – is mainly mentioned for his collaboration with Puccini to the Turandot’s libretto, as the thick collection of letters kept in the Livia Simoni Libary testifies.